Slicings of parallelogram polyominoes, or how Baxter and Schröder can be reconciled - Bouvel, Mathilde; Guerrini, Veronica; Rinaldi, Simone (Discrete mathematics and theoretical computer science, 2020)
We provide a new succession rule (i.e. generating tree) associated with Schröder numbers, that interpolates between the known succession rules for Catalan and Baxter numbers. We define Schröder and Baxter generalizations of parallelogram polyominoes (called slicings) which grow according to these succession rules. We also exhibit Schröder subclasses of Baxter classes, namely a Schröder subset of triples of non-intersecting lattice paths, and a new Schröder subset of Baxter permutations.